2017
DOI: 10.1016/j.jfda.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Biological actions and molecular effects of resveratrol, pterostilbene, and 3′-hydroxypterostilbene

Abstract: Stilbenes are a class of polyphenolic compounds, naturally found in a wide variety of dietary sources such as grapes, berries, peanuts, red wine, and some medicinal plants. There are several well-known stilbenes including trans-resveratrol, pterostilbene, and 3'-hydroxypterostilbene. The core chemical structure of stilbene compounds is 1,2-diphenylethylene. Recently, stilbenes have attracted extensive attention and interest due to their wide range of health-beneficial effects such as anti-inflammation, -carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(160 citation statements)
references
References 84 publications
5
131
0
14
Order By: Relevance
“…Furthermore, a drastic decline of p-mTOR/mTOR ratio and significantly increased protein levels of Beclin-1 were found. Although similar results were found in resveratrol-treated animals and the offspring after maternal resveratrol exposure [55,67], here it is shown that beneficial effects of resveratrol were maintained unexpectedly across generations. Of paramount importance is to demonstrate that molecular mechanisms implicated in transgenerational and intergenerational resveratrol effects occur through are the same that in direct contact with the polyphenol, reinforcing the importance of epigenetic machinery in the inheritance across generations.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, a drastic decline of p-mTOR/mTOR ratio and significantly increased protein levels of Beclin-1 were found. Although similar results were found in resveratrol-treated animals and the offspring after maternal resveratrol exposure [55,67], here it is shown that beneficial effects of resveratrol were maintained unexpectedly across generations. Of paramount importance is to demonstrate that molecular mechanisms implicated in transgenerational and intergenerational resveratrol effects occur through are the same that in direct contact with the polyphenol, reinforcing the importance of epigenetic machinery in the inheritance across generations.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, 4 flavonoid compounds (aesculin, phlorizin, coniferyl aldehyde, and eriodictyol) as well as 1 stilbene (pterostilbene) were detected for the first time in quinoa seeds, but their concentration was very low (range from 0.08 to 0.53 mg/kg DW). However, despite the low concentration, their role as chemopreventive and chemotherapeutic agents might be important (Tsai, Ho, & Chen, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Pterostilbene (3,5‐dimethoxy‐4′‐hydroxy‐ trans ‐stilbene) is a methylated analog of resveratrol with two methoxy groups on the A ring and one hydroxyl group on the B ring. Pterostilbene has been identified in blueberries and grape products and has attracted much attention because of its chemopreventive and chemotherapeutic effects . The substitution of the hydroxy groups with methoxy groups is believed to increase the stability and lipophilicity of pterostilbene compared to those of resveratrol, which leads to better membrane permeability, cellular uptake, and bioavailability .…”
Section: An Overview Of Resveratrol and Pterostilbenementioning
confidence: 99%
“…Pterostilbene has been identified in blueberries and grape products and has attracted much attention because of its chemopreventive and chemotherapeutic effects . The substitution of the hydroxy groups with methoxy groups is believed to increase the stability and lipophilicity of pterostilbene compared to those of resveratrol, which leads to better membrane permeability, cellular uptake, and bioavailability . The 3,5‐dimethoxy motif on the A phenyl ring of pterostilbene is considered important for its pro‐apoptotic activity in cancer cells .…”
Section: An Overview Of Resveratrol and Pterostilbenementioning
confidence: 99%